Development of a Framework for Safety Assessment of Mobile Mooring System - Silvianita, - (2012)
Mooring system is a vital component for the safety of floating structure. Mobile mooring system is responsible for the positioning of offshore platform. Therefore it is very essential to do the safety assessment of mobile mooring system. This paper studies a framework for safety assessment of mobile mooring system using HAZOP (Hazard Operability) and FTA (Fault Tree Analysis). HAZOP is a systematic examination of a system that is helpful to identify and evaluate risk related to accidents/incidents in mooring system. FTA is a deductive method for conducting safety assessment. The general objective of this paper is to evaluate the probability of failure of the mobile mooring system of semi submersible pipe lay barge. The primary objective of the HAZOP is to determine the direct causes of mooring failure. This information is then used to develop fault tree diagram in order to find the probability of mooring failure. To construct the FTA we obtained the knowledge and experience of experts on mobile mooring system. Based on the primary data, the top events for FTA of mobile mooring system are mooring line breakage (MLB), anchor failure (AF), anchor handling failure (AHF) and appurtenance connection failure (ACF). The result shows that the frequency of mooring system failure is classified as probable.